An undergraduate research experience in earth science education that benefits pre-service teachers and in-service earth science teachers. Issue 2 (3rd April 2023) - Ebert, James R.; Dolphin, Glenn; Bischoff, Paul
Abstract: Three cohorts of six pre-service Earth Science teachers (undergraduate majors in Earth Science Education) participated in summer research experiences focused on developing dynamic physical models of Earth processes to help middle and high school students understand complex concepts and confront misconceptions. The pre-service teachers used published criteria for evaluating models. Participants deepened their understanding of specific Earth Science concepts and broadened their perceptions of effective, student-centered, constructivist pedagogical practices through the use of models and model-based learning. Our pre-service Earth Science teachers achieved the same benefits that STEM majors report from their undergraduate research experiences, including better understanding of the nature of science, gains in problem-solving and communication skills, increased confidence, collaborative skills and comfort in working independently. Evaluation of the research experience via the Undergraduate Research Student Self-Assessment indicated that pre-service teachers reported higher gains than STEM majors in nearly all categories. The pre-service teachers presented the results of their projects to in-service teachers in professional development workshops at a science teachers' conference. In-service teachers' responses to these workshops were uniformly positive (98.2%; n = 57). Unlike most professional development activities in which participants benefit, but presenters may not, these professional development activities benefited participants and presenters alike.